Evaluation of Eustachian tube function in Behçet᾿s disease: A case-control study - Murat Yaşar; Fatma Atalay; Abdulvahap Kahveci; Zeynep Yavuz (Archives of Rheumatology, 2024)
Objectives: The purpose of this study was to evaluate Eustachian tube function in patients with Behçet’s disease (BD). Patients and methods: Forty-six patients (22 males, 24 females; mean age: 42.1±11.3 years; range, 19 to 64 years) with BD and 46 (21 males, 25 females; mean age: 38.5±14.8 years; range, 19 to 63 years) age- and sex-matched audiologically healthy individuals were enrolled in this cross-sectional, case-control study between June 2023 and August 2023. Demographic and clinical characteristics of participants were recorded from electronic health records. All participants completed the Eustachian tube function test and the Eustachian tube dysfunction questionnaire 7 (ETDQ-7). Binary logistic regression analysis was employed to identify the factors that predict Eustachian tube dysfunction in patients with BD. Additionally, the association between disease duration and ETDQ-7 scores was evaluated using Spearman’s rank correlation. Results: The median ETDQ-7 scores were significantly higher in patients with BD than in controls (10 (7-32) vs. 7 (7-9); p<0.001). The number of ears with Eustachian tube dysfunction was also significantly higher in the BD group than in the controls (n=22, 47.8% vs. n=7, 15.2%; p=0.007). Regression analysis did not reveal statistically significant factors that predicted Eustachian tube dysfunction. Moreover, no statistically significant correlation was observed between Eustachian tube dysfunction and disease duration (R=–0.067; p=0.525). Conclusion: This study showed that Eustachian tube dysfunction is more prevalent in patients with BD than in the healthy controls. However, clinical and demographic variables were not found to be associated with Eustachian tube dysfunction.